Diagnostik Streptokokus Hemolitik-Beta Group A dan Pola Resistensinya di Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT: Suparwoto Saleh, 1lyas and Tjarkiah Apandi . Diagnostics of group A beta-hemolytic streptococci and their resistence pattern in Yogyakafta Pharyngitis or impetigo caused by group A beta-hemolytic streptococci can incite acute rheumatic fever or acute glomerulonephritis. The Microbiology Department, Gadjah Mada University Faculty of Medicine, has identified and tested the sensitivity of group A beta-hemolytic streptococci to various antibiotics. Forty-one strains of group A beta-hemolytic streptococci (12.6%) resulted from 326 throat swabs could be isolated